Exploring Junior High School Students’ Engagement in Reading Activity By Using Picture Book: A Case Study - Kezia Cecilia Vanesa; Putri Praditya Utami; Iwan Ridwan (Jurnal Pendidikan dan Sastra Inggris, 2025)
The study examines the use of picture books in junior high school English reading activities, focusing on how teachers engage students and how students perceive them as a learning medium. The data is collected from a Karawang junior high school was collected through classroom observations, interviews, and thematic analysis. The findings suggest that teachers use picture books with appealing illustrations, relevant content, and group discussions to stimulate interest, improve focus, and promote social interaction and collaborative learning.